Penerapan Model Pembelajaran Problem Based Learning (PBL) Upaya Meningkatkan Hasil Belajar Siswa pada Materi Balaghah - Aufa, Nauwal; Maknuni, Jauharil (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
Classroom action research is a variety of classroom-context learning research carried out by teachers to solve learning problems faced by teachers. then the purpose of the study is how the application of the Problem-Based Learning (PBL) learning model attempts to improve student learning outcomes. In the first stage of learning activities using the problem-based learning model where student orientation to the problem serves to explain learning objectives and motivate students to get involved in problem-solving The results of observations of student attitudes in cycle I averaged 2.71 with a completion percentage of 65.60. While in cycle II it can be seen in the table above that the average student score is 2.78 while the percentage of completeness is 81.23. So that changes can be seen from each aspect of the attitude value in cycle II. In the knowledge value of cycle II, students have little understanding of the steps that must be done, students have started to participate in groups, cycle I lowest score is 25.00 while the highest score is 81.00 so the percentage of completeness is 59.0%. In cycle II the lowest score was 27.7 while the highest score was 86.60 so that the presentation of completeness was 75%.